AI for lawyers : how artificial intelligence is adding value, amplifying expertise, and transforming careers - Waisberg, Noah; Hudek, Alexander (John Wiley & Sons, Inc., 2021)
"The legal industry has been one of the slowest to adapt to today's data economy. It's a profession that is still bogged down in traditional, manual review processes and it bottle-necks organizations of all sizes with the staggering levels of business dependencies that rely on legal expertise. But this is changing. Technology - particularly Artificial Intelligence - is rapidly transforming the Legal profession and industry. Over $1.2B has been invested in legal technology in 2019, a record for annual investment in the space. AI for Lawyers is a guide to using artificial intelligence to transform a law firm or legal department, and in the process add tremendous value to any type of business. It explains how AI can help any organization win more business, exceed client expectations, drive greater efficiencies, risk management, and employee engagement by enabling them to do more meaningful work"--